2016
DOI: 10.1890/15-0330
|View full text |Cite
|
Sign up to set email alerts
|

Tree mortality from an exceptional drought spanning mesic to semiarid ecoregions

Abstract: Significant areas of the southern USA periodically experience intense drought that can lead to episodic tree mortality events. Because drought tolerance varies among species and size of trees, such events can alter the structure and function of terrestrial ecosystem in ways that are difficult to detect with local data sets or solely with remote-sensing platforms. We investigated a widespread tree mortality event that resulted from the worst 1-year drought on record for the state of Texas, USA. The drought affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…Recent severe droughts have led to increased tree mortality in forests worldwide and are predicted to be more common and impactful in the future (Allen et al 2015). In North America, many forest ecosystems have been affected by these events including southwestern U.S. pine forests (Breshears et al 2005), aspen forests in south-central Canada (Michaelian et al 2011), and diverse angiosperm and gymnosperm forests of Texas (Moore et al 2016) and California (Young et al 2017). It is difficult to generalize about regional vulnerability to extreme events in diverse forests with species varying in their strategy for surviving drought and sensitivity to insects and diseases (Anderegg et al 2016, Adams et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Recent severe droughts have led to increased tree mortality in forests worldwide and are predicted to be more common and impactful in the future (Allen et al 2015). In North America, many forest ecosystems have been affected by these events including southwestern U.S. pine forests (Breshears et al 2005), aspen forests in south-central Canada (Michaelian et al 2011), and diverse angiosperm and gymnosperm forests of Texas (Moore et al 2016) and California (Young et al 2017). It is difficult to generalize about regional vulnerability to extreme events in diverse forests with species varying in their strategy for surviving drought and sensitivity to insects and diseases (Anderegg et al 2016, Adams et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 2011 drought killed more than 300 million rural trees across Texas (Moore et al 2016). While predictions of future precipitation vary among different climate models, most agree that climate change is likely to result in increased temperatures with associated increases in evapotranspiration and water demand (Sun et al 2008).…”
Section: Forestsmentioning
confidence: 99%
“…Wu et al (2016), by combining elaborate ground and tower measurements with remotely sensed data across a rainfall gradient, found that coordinated leaf development and demography may explain large increases in ecosystem photosynthesis during dry conditions. An all-data approach such as this, where remote sensing methods are leveraged with other supplementary data streams, including ground-based measurements, may represent the most promising approach for cohesively and coherently addressing drought effects at broad scales (AghaKouchak et al, 2015;Cohen et al, 2016;Moore et al, 2016). A number of integrated wide-area monitoring systems have been developed that loosely follow this type of conceptual model, including the US Drought Monitor and the related North American Drought Monitor (Lawrimore et al, 2002).…”
Section: Remote-sensing-based Measures Of Droughtmentioning
confidence: 99%
“…This drought was remarkable because of its severity and duration, and because of the extensive area burned during the 2011 wildfire season (Nielsen-Gammon, 2012). An estimated 6.2% of all live trees died statewide (Moore et al, 2016). Where and when they co-occur, drought and wildfire may have additive or redundant effects in reducing NDVI.…”
Section: Wildland Fire Datasetsmentioning
confidence: 99%
See 1 more Smart Citation